HUBUNGAN KUALITAS PELAYANAN KEPERAWATAN DENGAN KEPUASAN PASIEN - Rahayu, Sri Hartati; Wijaya, Leni (LPPM STIKes Mitra Adiguna, 2025)
Customer or patient satisfaction is a person's feeling of satisfaction or disappointment after comparing service performance to expected performance. Service quality cannot be separated from customer satisfaction. The aim of this research is to determine the relationship between the quality of nursing services and patient satisfaction in the emergency room at Pusri Hospital in 2024. The research method uses quantitative analytical methods with a cross sectional approach. The population in this study were all patients who came in January 2024. Sampling was taken using a purposive sampling method with a total sample of 96 respondents. The research results showed that the frequency distribution of the majority of respondents stated that they were satisfied, 62 respondents (64.6%), the majority of respondents received good quality nursing services, 72 respondents (75%). The results of the chi square statistical test showed that there was a relationship between the quality of nursing services and patient satisfaction in the emergency room at Pusri Hospital, Palembang in 2024 with p.value = 0.003 and OR = 4.649. It is hoped that it can contribute ideas to Pusri Palembang Hospital to improve the quality of nursing services in order to meet the expectations and satisfaction of patients, especially those undergoing treatment in the emergency room, so that they can determine the next steps to be taken in measuring policy in the future, especially in terms of nurse responsiveness. towards patients and nurses' skills in handling patients to be further improved so as to increase patient satisfaction.